Hubungan Aktivitas Fisik dengan Kualitas Tidur Penderita DM Tipe 2 di Wilayah Kerja Puskesmas Cijulang - Herry Garna; Eva Rianti Indrasari; Delia Oktaviani Solihat (Bandung Conference Series: Medical Science, 2023)
Abstract: High physical activity affects sleep quality clinically, while sleep quality is also affected by sleep disturbances at night caused by diabetes mellitus (DM) which is generally experienced by the elderly with less physical activity. The purpose of this study was to analyze the relationship between physical activity and sleep quality in patients with type 2 DM in the working area of ​​the Cijulang Health Center for the period of July 2022. The study used a quantitative sampling method of observation analysis using a questionnaire instrument with a cross sectional approach design. There were 58 type 2 DM sufferers who participated in the study with an average age of 60 years having high activity as much as 34 (59%) type 2 DM sufferers based on the results of the Global Physical Activity Questionnaire and 30 (52%) type 2 DM sufferers had good sleep quality according to the results of calculating the Pittsburgh Sleep Quality Index. Based on the results of the Pearson Correlation analysis, it shows correlation coefficients with a value of strong closeness (r=0.726) and significance (p=0.000). In conclusion, there is a relationship between physical activity and sleep quality in patients with type 2 DM. The higher the physical activity, the better the quality of sleep obtained. Keywords: DM type 2; physical activity; sleep quality